Implementasi Pendidikan Multikultur dalam Meningkatkan Rasa Toleransi Antar Mahasiswa PPKn di Lingkungan Kampus Unila - Naufal Daffa (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2024)
The diversity of cultures, ethnicities, religions and traditions inherent in the life of the Indonesian nation makes multicultural education an urgent need, especially in higher education environments. This article discusses the implementation of multicultural education in building and increasing a sense of tolerance among students of the Pancasila and Citizenship Education Study Program (PPKn). This research uses qualitative methods with interviews as the main instrument. Based on research results, multicultural education is implemented through three main approaches, namely integration of multicultural curriculum, strengthening cross-cultural activities, and optimizing the role of lecturers as diversity facilitators. This strategy has proven effective in building students' critical awareness of the importance of respecting differences. Interview results revealed that students felt more open to diversity after participating in cross-cultural activities and inclusive class discussions. However, challenges are still found in its implementation, such as the existence of stereotypes and a lack of in-depth understanding of the multicultural concept. This article concludes that multicultural education is not only important for creating tolerance in the campus environment, but is also an important provision for PPKn students as prospective educators and agents of social change. The recommendations given include strengthening training for lecturers, developing modules based on real experience, and increasing the frequency of cross-cultural programs.